Domestic Resource Mobilization and the Poor - Lustig, Nora (World Bank, Washington, DC, 2017)
At the UN General Assembly of September 2015, countries around the world committed to the Sustainable Development Goals (SDGs). By 2030, counties committed to attain poverty and hunger eradication, healthy lives, quality education, gender equality and sustainable development. Countries also committed to promoting full-employment growth, decent work, peaceful societies and accountable institutions as well as to reducing inequality and strengthening global partnerships for sustainable development. One key factor to achieving the SDGs will be the availability of fiscal resources to deliver the floors in social protection, social services and infrastructure embedded in the SDGs. A significant portion of these resources is expected to come from domestic sources in developing countries themselves, complemented by transfers from the countries that are better off. The report states that for all countries, the mobilization and effective use of domestic resources is at the crux of our common pursuit of sustainable development and achieving the SDGs Moreover, countries will be expected to set spending targets to deliver social protection and essential public services for all and set nationally defined domestic revenue targets.In particular, that raising additional revenues domestically for infrastructure, protecting the environment or social services may leave a significant portion of the poor with less cash to buy food and other essential goods. It is not uncommon that the net effect of all governments taxing and spending is to leave the poor worse off in terms of actual consumption of private goods and services. Achieving the new Sustainable Development Goals will depend in part on the ability of governments to improve their tax collection and enforcement systems. However, demand for investments into infrastructure and public services must be balanced against the competing need to protect low-income households that may otherwise be made worse off from misaligned tax and transfer policies.